Influence of Interleukin-6 (IL-6) Promoter Gene Polymorphisms (−174G>C, −572G>C, and −597G>A) on IL-6 Plasma Levels and Their Impact in the Development of Acute Ischemic Stroke in Young Indians. (18th June 2019) - Akhter, Mohammad Suhail; Biswas, Arijit; Abdullah, Saleh Mohammed; Hobani, Yahya; Ranjan, Ravi; Behari, Madhuri; Saxena, Renu
This study aimed to determine whether there is an influence of interleukin 6 ( IL-6 ) gene promoter polymorphisms on IL-6 plasma levels and its role in the development of ischemic stroke in young Indians. One hundred young patients with ischemic stroke (age ≥ 45 years) and equal number of age- and sex-matched controls were genotyped for 174G>C, −572G>C, and −597G>A promoter polymorphisms by polymerase chain reaction–restriction fragment length polymorphism. Plasma IL-6 levels were measured by enzyme-linked immunosorbent assay. Plasma IL-6 levels were significantly higher in patients as compared to controls (patients: 28.61 ± 8.61 pg/mL, controls: 7.60 ± 4.10 pg/mL, P = .001). Both −174G>C (allelic χ 2 / P value: 4.79/.028, genotypic χ 2 / P value: 5.3/.021) and −572G>C (allelic χ 2 / P value: 9.63/.00113 Genotypic χ 2 / P value: 74/.0002) polymorphisms exhibited genotypic as well as allelic significant association with the disease phenotype. Comparison was made between patients and controls for all 3 polymorphisms using a recessive model with respect to plasma IL-6 levels; no polymorphism showed any significant correlative association with the increased IL-6 levels ( P = .31, .51, .32). Interleukin 6 is an inflammatory marker that is considerably influenced by nongenetic factors and is not a good candidate gene for studying genetic components associated with ischemic stroke. It seems that the variability in IL-6 levels is an integrated effect of nongenetic influences and the inflammatory events that follow ischemic stroke instead of being its cause. It is suggested that there is no direct association between −174G>C, −572G>C, and −597G>A polymorphisms and elevated IL-6 levels in the development of ischemic stroke.